PENGARUH KUALITAS PELAYANAN DAN KETEPATAN PENGIRIMAN TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA PENGIRIMAN BARANG AGEN SAP EXPRESS BINJAI UTARA DI MASA PANDEMI COVID-19 - Muhammad Sugiato; Suwarno Suwarno; Dewi Nurmasari Pane (Ensiklopedia Education Review, 2021)
Business people in Indonesia certainly know how courier services have a big influence on their business. Especially if the business is engaged in e-commerce or other sales. Especially if the business is done online, the delivery factor becomes very important. Only the process of sending goods is carried out manually. Not only that, e-commerce efforts which incessantly always offer promos including free shipping (postage), are believed to be able to increase the attractiveness of people to switch to online shopping. Accompanied by media and technology support that is increasingly adequate in the current era. Along with the increasing intensity of transactions through e-commerce, the number of shipments using its services also increased by 40%. Based on the results of the analysis of the data that has been obtained by the researcher, it can be concluded that the Service Quality variable (X1) and the Delivery Accuracy variable (X2) have an effect on Customer Satisfaction (Y) with a value of 41.2% while 58.8% is influenced by factors or other variables not examined by this study.Keywords: Service Quality, Delivery Accuracy, Customer Satisfaction